The downregulation of sweet taste receptor signaling in enteroendocrine L-cells mediates 3-deoxyglucosone-induced attenuation of high glucose-stimulated GLP-1 secretion. (20th October 2018) - Wang, Fei; Song, Xiudao; Zhou, Liang; Liang, Guoqiang; Huang, Fei; Jiang, Guorong; Zhang, Lurong
Abstract: Context: Sweet taste receptors (STRs) involve in regulating the release of glucose-stimulated glucagon-like peptide-1 (GLP-1). Our in vivo and in vitro studies found that 3-deoxyglucosone (3DG) inhibited glucose-stimulated GLP-1 secretion. Objective: This study investigated the role of STRs in 3DG-induced inhibition of high glucose-stimulated GLP-1 secretion. Methods: STC-1 cells were incubated with lactisole or 3DG for 1 h under 25 mM glucose conditions. Western blotting was used to study the expression of STRs signaling molecules and ELISA was used to analyse GLP-1 and cyclic adenosine monophosphate (cAMP) levels. Results: Lactisole inhibited GLP-1 secretion. Exposure to 25 mM glucose increased the expressions of STRs subunits when compared with 5.6 mM glucose. 3DG decreased GLP-1 secretion and STRs subunits expressions, with affecting other components of STRs pathway, including the downregulation of transient receptor potential cation channel subfamily M member 5 (TRPM5) expression and the reduction of intracellular cAMP levels. Conclusion: 3DG attenuates high glucose-stimulated GLP-1 secretion by reducing STR subunit expression and downstream signaling components.